TECHNOLOGY AND TECHNOLOGICAL CAPABILITIES IN SUPPLY CHAIN MANAGEMENT - Roberto Giro Moori; Professor VITORINO; JOÃO BATISTA CAMARGO (Faces: Revista de Administração, 2023)
The article aims to analyze the mediating effect of technologies and technological capabilities on the relationship between supply chain strategic orientation and chain performance and its impact on the target company performance. To collect data, a sample of 125 manufacturing companies sited in technological hubs in Brazil was used. The data, treated by modeling in structural equations, revealed that technology and technological capabilities mediate the relationship between the strategic orientation and the supply chain performance, in turn, impacts the focal company performance. Given these results, it was concluded that technology and technological capabilities are the best strategies to improve the relationship between the strategic orientation of the supply chain and performances for chain and company. The contribution of this paper was proof that technology and technological capabibilities play an important role in performances both for the supply chain and the focal company.